SET domain containing 1B gene is mutated in primary hepatic neuroendocrine tumors. Issue 11 (17th May 2019) - Yang, Penghui; Huang, Xuanlin; Lai, Chengcai; Li, Lin; Li, Tieling; Huang, Peide; Ouyang, Songying; Yan, Jin; Cheng, Sijie; Lei, Guanglin; Wang, Zhaohai; Yu, Linxiang; et al.
Abstract : Primary hepatic neuroendocrine tumors (PHNETs) are extremely rare NETs originating from the liver. These tumors are associated with heterogeneous prognosis, and few treatment targets for PHNETs have been identified. Because the major genetic alterations in PHNET are still largely unknown, we performed whole‐exome sequencing of 22 paired tissues from PHNET patients and identified 22 recurring mutations of somatic genes involved in the following activities: epigenetic modification ( BPTF, MECP2 and WDR5 ), cell cycle ( TP53, ATM, MED12, DIDO1 and ATAD5 ) and neural development ( UBR4, MEN1, GLUL and GIGYF2 ). Here, we show that TP53 and the SET domain containing the 1B gene ( SETD1B ) are the most frequently mutated genes in this set of samples (3/22 subjects, 13.6%). A biological analysis suggests that one of the three SETD1B mutants, A1054del, promotes cell proliferation, migration and invasion compared to wild‐type SETD1B . Our work unveils that SETD1B A1054del mutant is functional in PHNET and implicates genes including TP53 in the disease. Our findings thus characterize the mutational landscapes of PHNET and implicate novel gene mutations linked to PHNET pathogenesis and potential therapeutic targets. Abstract : What's new? Neuroendocrine tumors often metastasize to the liver but primary hepatic neuroendocrine tumors are extremely rare. Here the authors sequenced tumors from 22 patients in China and provide a first look at the mutational landscape of primary hepatic neuroendocrine tumors. The study points to a possible etiological role of the SET domain containing 1B gene (SETD1B) as it was among the most frequently mutated genes, a role that needs to be further explored.